Evaluating depression- and anxiety-like behaviors in non-human primates - Ausderau, Karla K.; Colman, Ricki J.; Kabakov, Sabrina; Schultz-Darken, Nancy; Emborg, Marina E. (Frontiers in Behavioral Neuroscience, 2023)
Depression and anxiety are some of the most prevalent and debilitating mental health conditions in humans. They can present on their own or as co-morbidities with other disorders. Like humans, non-human primates (NHPs) can develop depression- and anxiety- like signs. Here, we first define human depression and anxiety, examine equivalent species-specific behaviors in NHPs, consider models and current methods to identify and evaluate these behaviors. We also discuss knowledge gaps, as well as the importance of evaluating co-occurrence of depression- and anxiety- like behaviors in animal models of human disease. Lastly, we consider ethical challenges in depression and anxiety research on NHPs in order to ultimately advance the understanding and the personalized treatment of these disorders.